2006
DOI: 10.4049/jimmunol.176.12.7542
|View full text |Cite
|
Sign up to set email alerts
|

Group B Streptococcus Induces Macrophage Apoptosis by Calpain Activation

Abstract: Group B Streptococcus (GBS) has developed several strategies to evade immune defenses. We show that GBS induces macrophage (Mφ) membrane permeability defects and apoptosis, prevented by inhibition of calcium influx but not caspases. We analyze the molecular mechanisms of GBS-induced murine Mφ apoptosis. GBS causes a massive intracellular calcium increase, strictly correlated to membrane permeability defects and apoptosis onset. Calcium increase was associated with activation of calcium-dependent protease calpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
111
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(117 citation statements)
references
References 72 publications
6
111
0
Order By: Relevance
“…The following antibodies were used for immunoblotting or immunocytochemistry: mouse monoclonal anti-E-cadherin (DECMA-1 clone), rabbit polyclonal anti-pan-cadherin, and mouse monoclonal anti-␤-catenin (all from Sigma) and mouse monoclonal anti-pan-actin (Thermo Fisher Scientific, Waltham, MA). The selective calpain inhibitor PD150606 (EMD, Darmstadt, Germany) was used at a concentration of 50 M 30 min prior to infection (13). TL2.1, a neutralizing monoclonal antibody against TLR2 (10 g/ml; eBioscience, San Diego, CA) was used 1 h prior to infection.…”
Section: Methodsmentioning
confidence: 99%
“…The following antibodies were used for immunoblotting or immunocytochemistry: mouse monoclonal anti-E-cadherin (DECMA-1 clone), rabbit polyclonal anti-pan-cadherin, and mouse monoclonal anti-␤-catenin (all from Sigma) and mouse monoclonal anti-pan-actin (Thermo Fisher Scientific, Waltham, MA). The selective calpain inhibitor PD150606 (EMD, Darmstadt, Germany) was used at a concentration of 50 M 30 min prior to infection (13). TL2.1, a neutralizing monoclonal antibody against TLR2 (10 g/ml; eBioscience, San Diego, CA) was used 1 h prior to infection.…”
Section: Methodsmentioning
confidence: 99%
“…We further studied the mechanisms of -calpain activation in soft substrate by utilizing inhibitors acting at different target sites of calapin. PD150606 and PD151746, two specific inhibitors targeting Ca 2ϩ -binding site of calpain (Fettucciari et al, 2006), inhibited soft substrate-induced calpain activation in a dosedependent manner ( Figure 3C). PD145305, a negative control for PD150606 and PD151746 (Fettucciari et al, 2006), did not show any effect on the activation of calpain.…”
Section: Soft Substrate-induced Apoptosis Results From -Calpain Activmentioning
confidence: 95%
“…PD150606 and PD151746, two specific inhibitors targeting Ca 2ϩ -binding site of calpain (Fettucciari et al, 2006), inhibited soft substrate-induced calpain activation in a dosedependent manner ( Figure 3C). PD145305, a negative control for PD150606 and PD151746 (Fettucciari et al, 2006), did not show any effect on the activation of calpain. In contrast, ALLN, an inhibitor targeting catalytic binding site of calpain (Debiasi et al, 1999), showed no significant effect on soft substrate-induced calpain activity.…”
Section: Soft Substrate-induced Apoptosis Results From -Calpain Activmentioning
confidence: 95%
“…Calpain activation downstream of TLRs in macrophages has implicated these proteases in regulating apoptosis and phagocytosis [13,20,21]. To test whether defects in FIP response of calpain KO mice relate to defects in macrophages, we isolated peritoneal macrophages from WT and KO mice, and subjected them to enterobacterial infection ex vivo (using bacterial cultures employed in FIP model).…”
Section: Calpain Ko Macrophages Show Delayed Bacterial Killing Responsementioning
confidence: 99%
“…In macrophages, calpain activation leads to cleavage of Selenoprotein K (SelK) [13], a transmembrane endoplasmic reticulum protein implicated in regulating Ca ++ flux, ROS production, and cell motility [19]. Calpain activation also allows Group B Streptococcus to evade killing by inducing caspase-independent apoptosis, disruption of the cytoskeleton, and phagosome escape in macrophages [20,21]. Another key calpain substrate relevant to chronic inflammation and immunity is IL-1α, which lacks a signal peptide, undergoes proteolysis in the cytoplasm, and is secreted by both activated and dying cells [22].…”
mentioning
confidence: 99%